Adult Muscle Stem Cells: Exploring the Links Between Systemic and Cellular Metabolism - Purohit, Gunjan; Dhawan, Jyotsna (Frontiers in Cell and Developmental Biology, 2019)
Emerging evidence suggests that metabolites are important regulators of skeletal muscle stem cell (MuSC) function and fate. While highly proliferative in early life, MuSC reside in adult skeletal muscle tissue in a quiescent and metabolically depressed state, but are critical for the homeostatic maintenance and regenerative response of the tissue to damage. Metabolic activity in MuSC changes with their functional activation but the spatio-temporal links between physiological metabolism and stem cell metabolism require explicit delineation. The quiescent MuSC is defined by a specific metabolic state, which is controlled by intrinsic and extrinsic factors during physiological and pathological tissue dynamics. Interesting would be to know the extent of tissue and organismal level changes driven by alteration in metabolic state of quiescent MuSC. Metabolites are key regulators of epigenetic mechanisms and chromatin state is known to affect muscle regenerative capacity. In this review, we explore the links between cell intrinsic, tissue-level and systemic metabolic state in the context of MuSC epigenetics, quiescence and tissue homeostasis to highlight unanswered questions.